Black belt web programming methods - Techniques, Web.; Tech, Web. ([S.l.] : Publishers Group West, 1997)
This guide discusses the special programming approaches required to create successful Web sites. It includes reusable code, and provides practical advice on the tools and techniques needed to "do it right". It is a collection of advice by teachers of the Software Development Conference. The book is part of a series which brings together practical techniques and advice from experienced programmers in selected areas of software development. It draws on a library of expertise from professional conferences and programming journals. Each collection presents useful and current information about its specific topic. This collection of advice and techniques is from master programmers who write for "Web Techniques" magazine. It includes practical advice on the tools and techniques needed to develop powerful Web sites. Expectations for Web sites are becoming more sophisticated, ever-more complex programming is required to meet these expectations. The book provides the knowledge that developers need to create user-friendly and secure commerce systems, useful databases, on-the-fly cutomized Web pages, multimedia presentations, and other essential elements of current Web development. Key topics of the book include: security methods for the Web; hypertext transaction designs; easy-to-use databases; distributed objects; and automated Web site maintenance.